One‐Pot Fabrication of Crumpled N‐Doped Graphene Anchored with Cobalt for High‐Performance Lithium–Sulfur Batteries. Issue 7 (7th April 2020) - Mao, Wutao; Ma, Chao; Ni, Ping; Li, Maolong; Ding, Yiming; Zhang, Shaojie; Pan, Junli; Cao, Fengpu; Bao, Keyan
Abstract: The commercialization of sulfur batteries is hindered by a few inherent drawbacks. In this study, crumpled N‐doped graphene anchored with cobalt (Co‐NCG) was fabricated in one pot via a sample solvothermal method and applied to lithium‐sulfur (Li−S) batteries. The crumpled structure not only gives graphene a large specific surface area and abundant pores, but also endows graphene superb stability by preventing its restacking; these features are beneficial for loading and efficient utilization of sulfur. The lone pair electrons on the nitrogen atom underwent strong chemical interactions with Li ions, which lent the Co‐NCG/S material the ability to chemically immobilize polysulfide species. Cobalt acts as an electrocatalyst in the battery and kinetically accelerates sulfur redox reactions. As a result of these multifunctional arrangements, the Co‐NCG/S cathode showed excellent capacity retention and reaction kinetics and high sulfur loading capacity. Abstract : Crumpled N‐doped graphene anchored with cobalt was fabricated in one pot and applied to Li−S batteries. The composite cathode showed excellent capacity retention and reaction kinetics. The crumpled structure is beneficial for loading and efficient utilization of sulfur. Cobalt acts as an electrocatalyst and kinetically accelerates sulfur redox reactions. The lone pair electrons on N have the ability to chemically fix polysulfide.